Comparison of the reproductive ability and mortality of the Varroa destructor mite in worker and drone brood cells in Africanized honey bees of Costa Rica - Calderón, Rafael A. (2014)
The reproduction of the mite Varroa destructor was studied in worker and drone brood cells of Africanized honey bees. In addition, the mortality of mite offspring was evaluated, particularly male absence or mortality. The study was conducted from March to December 2010, using 15 colonies located at Barreal de Heredia and Ciudad Colón, San José. A total of 388 worker cells and 403 drone cells naturally infested by an adult male mite were examined. Mite reproduction was studied using the following parameters: fertility, fecundity, production of viable female offspring, production of immature offspring, production of only female or only male offspring, and no reproduction at all. Fertility of V. destructor infesting worker brood was 88.9% and average fecundity was 3.2 descendants per mite. On the other hand, mite fertility in drone brood was 93.1% and average fecundity was 4.0 descendants per mite. In worker cells, 37.6% of mites produced viable female offspring, 14.7% non-viable female offspring, 4.6% immature offspring and 32.0% offspring of only one sex. Of the mites that reproduced in drone brood, 64.8% produced viable female offspring, 5.2% non-viable offspring, 1.0% immature offspring, and 22.1% offspring of only one sex. In addition, in worker cells high mortality was observed in the mobile protonymph (66.4%), immobile protonymph (45.2%), mobile deutonymph, and adult male (23.9%). Male absence or mortality was determined in 40.0% of the worker cells with reproduction. In drone brood, mite mortality was recorded mainly in the mobile protonymph (78.4%) and immobile protonymph (42.6%). Male absence or mortality was determined in 21.3% of the drone cells with reproduction. Mite fertility was similar in both worker and drone brood. Nevertheless, the number of viable females produced per mite was higher in drone brood compared to worker brood. On the other hand, male absence or mortality was significantly higher in worker cells. This indicates that reproduction of the V. destructor mite was more successful with drone brood, which makes it more suitable for mite reproduction.